2007
DOI: 10.1038/ncb1555
|View full text |Cite|
|
Sign up to set email alerts
|

HCLK2 is essential for the mammalian S-phase checkpoint and impacts on Chk1 stability

Abstract: Here, we show that the human homologue of the Caenorhabditis elegans biological clock protein CLK-2 (HCLK2) associates with the S-phase checkpoint components ATR, ATRIP, claspin and Chk1. Consistent with a critical role in the S-phase checkpoint, HCLK2-depleted cells accumulate spontaneous DNA damage in S-phase, exhibit radio-resistant DNA synthesis, are impaired for damage-induced monoubiquitination of FANCD2 and fail to recruit FANCD2 and Rad51 (critical components of the Fanconi anaemia and homologous recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
141
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(162 citation statements)
references
References 50 publications
16
141
2
Order By: Relevance
“…Previous studies have shown that Chk1 is degraded by the ubiquitinproteasome system and that this can be stimulated by phosphorylation of the protein at S345 (18)(19)(20)(21)(22). Because we had observed a decrease in phospho-Chk1 at earlier time points after Atg7 recombination, we reasoned this may be due to enhanced degradation of the protein, which over time would then have an impact on the total pool of Chk1 under conditions where DNA-damage signaling would be enhanced after a prolonged loss of autophagy.…”
Section: Significancementioning
confidence: 66%
“…Previous studies have shown that Chk1 is degraded by the ubiquitinproteasome system and that this can be stimulated by phosphorylation of the protein at S345 (18)(19)(20)(21)(22). Because we had observed a decrease in phospho-Chk1 at earlier time points after Atg7 recombination, we reasoned this may be due to enhanced degradation of the protein, which over time would then have an impact on the total pool of Chk1 under conditions where DNA-damage signaling would be enhanced after a prolonged loss of autophagy.…”
Section: Significancementioning
confidence: 66%
“…In Caenorhabditis elegans, hypomorphic mutants of the Tel2 ortholog (Clk-2/Rad-5) were also reported to show extended life span and hypersensitivity to UV irradiation (29,30). Subsequent studies showed that Tel2 is essential for growth (31), and its homologs are important for DNA replication checkpoint in S. pombe, C. elegans, and mammalian cells (32)(33)(34). Recently, it was reported that mammalian Tel2 interacts with and regulates the stability of all PIKK family proteins (19).…”
Section: Tti1 Interacts With Tel2 and Is Important For Tel2-mtor Assomentioning
confidence: 99%
“…The discovery that S. pombe and mammalian Tel2 interact directly with all phosphatidylinositol 3-kinase related protein kinase (PIKK) family members (which include ATM, ATR, DNA-PKcs, mTOR, FRAP and SMG1) raised the possibility that Tel2 may act as a universal regulator of the PIKK family of kinases. [3][4][5] A recent study has shown that conditional loss of Tel2 in mouse embryonic fibroblast (MEF) cells results in the dramatic reduction in protein levels of all PIKK family members. 5 This finding led de Lange and colleagues to propose that Tel2 is a highly conserved regulator of PIKK stability.…”
Section: Differential Regulation Of the Pikk Kinase Family By Tel2mentioning
confidence: 99%
“…Subsequent studies in many organisms have demonstrated a conserved role for Tel2 in the DNA damage checkpoint response. [2][3][4][5] The absence of recognizable domains in Tel2 has been a major hindrance in understanding how it is able to operate at the molecular level. The discovery that S. pombe and mammalian Tel2 interact directly with all phosphatidylinositol 3-kinase related protein kinase (PIKK) family members (which include ATM, ATR, DNA-PKcs, mTOR, FRAP and SMG1) raised the possibility that Tel2 may act as a universal regulator of the PIKK family of kinases.…”
Section: Differential Regulation Of the Pikk Kinase Family By Tel2mentioning
confidence: 99%
See 1 more Smart Citation